Knowledge and attitudes of high school learners regarding people living with HIV/AIDS - Fana, Thanduxolo Elford (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2010.